Microlearning through TikTok in Higher Education. An evaluation of uses and potentials - Conde-Caballero, David; Castillo-Sarmiento, Carlos A.; Ballesteros-Yánez, Inmaculada; Rivero-Jiménez, Borja; Mariano-Juárez, Lorenzo (Education and information technologies, 2024)
While social media is evolving rapidly, understanding its underlying and persistent features with the potential to support high-quality learning would provide opportunities to enhance competence acquisition and collaborative work in higher education. Moreover, the adoption of tools that students already use in their everyday lives facilitates the integration of new forms of learning. In this context, we have developed an initiative to disseminate content through TikTok in three modules of the Bachelor's Degree in Nursing course, with the aim of promoting quality learning through these microlearning environments. To this end, we have implemented these learning environments and evaluated the users’ perceptions, as well as their level of acceptance of the technology according to the Technology Acceptance Model. Overall, our results show high levels of satisfaction with regard to engagement and the content generated, as well as in terms of the acceptance of the technology. Our results do not show gender-specific variations, but we did detect slight variations depending on the subject in which the microlearning tool was deployed. Although for the most part these variations do not change the participants' assessment of their experience, it will be necessary in the future to determine the underlying reasons for these variations. In addition, our results suggest that it is possible to design a content creation system to promote quality learning through microlearning that can be transferred to other subjects, at least in the Bachelor's Degree in Nursing.